The psychological construction of emotion - Barrett, Lisa Feldman; Russell, James A.
"This volume presents cutting-edge theory and research on emotions as constructed events rather than fixed, essential entities. It provides a thorough introduction to the assumptions, hypotheses, and scientific methods that embody psychological constructionist approaches. Leading scholars examine the neurobiological, cognitive/perceptual, and social processes that give rise to the experiences Western cultures call sadness, anger, fear, and so on. The book explores such compelling questions as how the brain creates emotional experiences, whether the "ingredients" of emotions also give rise to other mental states, and how to define what is or is not an emotion. Introductory and concluding chapters by the editors identify key themes and controversies and compare psychological construction to other theories of emotion"--